AGENDAMENTO E INTERAGENDAMENTO TEMÁTICO NO PROCESSO DE PRODUÇÃO JORNALÍSTICA NO TELEJORNALISMO REGIONAL - Anjos, Manoel Moabis Pereira dos (2015)
This study investigates the scheduling process in four television news the State of Paraná, produced by two different stations: RPC TV and SBT. The news programs are: Paraná TV 1st and 2nd edition and Tribune of Massa 1st and 2nd edition. The objective of this research is to analyze how the newsrooms studied relate to other news organizations and to each other, from the selection and construction of the journalistic agenda. The study permeates the discussions on competition, editorial line and journalistic sources. For this, the participant observation was used as a methodological tool, having a theoretical framework based on studies of Newsmaking, Scheduling (Agenda-setting) and values-news. The dissertation shows the presence of inter scheduling between the newscasts of competing stations, highlighting the placement of the same agenda and the same sources of information.